Avaliação institucional: interlocução entre auto-avaliações na perspectiva do SINAES e do GESPÚBLIC - Farias Filho, Alberto (2011)
The institutional assessment, focusing on self-assessment is an instrument for improving the management of federal higher education intuitions. This dissertation is a description of the intersection between the two forms of self-assessment prescribed by a National Assessment System of Higher Education (SINAES) and the other advocated by the National Public Management and Debureaucratization (GESPÚBLICA), which allow to draw knowledge that can be applied in practice to be carried out participatory planning and analyzes the data collected from the sources indicated, trying to answer the question generating, from the subject, and clarify how is dialogue between self-assessments: in view of SINAES and the GESPÚBLICA. The points of interaction between those instruments are highlighted, as well as the synergy between the tools that allows you to create mechanisms to promote alignment of management processes with the mission and developing a plan to improve the management, with a hierarchy of priorities that can be generated from the synergy between the instruments of institutional self-evaluation.